Application Of Allo Mesenchymal Stem Cells On Chronic Burn Wound: Case Series Report - Wardhana, Aditya; Liem, Isabella Kurnia; Feroniasanti, Lauda; Pudjiti, Dyah Juliana; Mujadid, Fajar; Kispa, Tera; Novialdi, Novialdi (Jurnal Plastik Rekonstruksi, 2017)
Background : Severe burns are among the commonly occurring trauma with lethal outcome. One of the important aspects of severe burn therapy is to quickly achieve wound healing. Previous reports indicated that mesenchymal stem cells (MSCs) therapy contributes in facilitating better wound healing. In this report, we investigated the effects of MSCs derived from human bone marrow and umbilical cord on wound healing in patients with severe burns and its mechanism. Method : We performed human bone marrow and human umbilical cord MSCs therapy on 3 severe burns patients. Two of the patients had inadequate donor to close raw surface with skin graft, whilst one patient had infected chronic burn wound which have failed to epithelialize despite repeated attempts of skin graft and wound care. Result : We observed that MSCs therapy significantly accelerated wound healing. The effects after MSCs migrated into wound were decreased infiltration of inflammatory cells and faster epithelialization. Conclusion : This study suggests that MSCs therapy has positive effects in improving wound healing in severe burns patients. Data provided by this research may serve as theoretical basis for further study of MSCs application in burn wound therapy.